THU0444 Assessment of Global Disease Activity in RA by Patients and Physicians: Cultural Differences across Countries in the Meteor Database. (10th June 2014) - Gvozdenovic, E.; Allaart, C.; Wolterbeek, R.; Brenol, C.; Chopra, A.; Dougados, M.; Emery, P.; Ferraccioli, G.; Van Der Heijde, D.; Huizinga, T.; Kay, J.; Mola, E.; et al.
Abstract : Background: Dissonant perceptions of disease activity between rheumatoid arthritis (RA) patients and their rheumatologists may influence treatment decisions. The discordance between patient's and physician's global disease activity assessment (PtGDA and PhGDA, respectively) may vary by country because of cultural differences. Objectives: To compare the differences between PtGDA and PhGDA among 13 countries in the METEOR database. Methods: The Measurement of efficacy of Treatment in the Era of Rheumatology (METEOR) database, a worldwide online tool for disease monitoring in RA, was used to anonymously select 23, 117 visits in 5, 709 patients during the period between 2008 and 2012. PtGDA and PhGDA were scored independently on a 100 mm visual analogue scale (VAS) with 0 and 100 as extremes. Linear Mixed Models (LMM) were used to estimate the mean differences between PtGDA and PhGDA score in13 countries (Brazil, Czech Republic, Spain, France, United Kingdom, Ireland, Italy, Latvia, Mexico, Pakistan, Portugal, United States, and the Netherlands), adjusted for DAS. Generalized Estimated Equation (GEE) was used to model differences (>20mm) between PtGDA and PhGDA score as the outcome and countries as determinants, corrected for DAS. Results: Mean difference between PtGDA and PhGDA score differs by country, varying from -2 mm (physician scores higher) in Mexico to 14 mm (patient scores higher) in Brazil (Figure 1 ), independent of DAS. GEE indicated that "country" was a significant determinant of the difference between PtGDA and PhGDA score, independent of differences in DAS. With the Netherlands as a reference, PtGDA and PhGDA scores differ significantly within the same patient in almost all countries (Brazil, Czech Republic, Great Britain, Ireland, Italy, Latvia, Mexico, Pakistan, Portugal and United States). Conclusions: We find differences between patients' and physicians' assessment of global disease activity, the magnitude of which varies depending upon the country in which the patient and the physician both reside. Cultural influences must be taken into account when interpreting discordances between the patient's and the physician's assessment of global disease activity in RA. Although the magnitude differs across countries, patients nearly always assess global disease activity to be worse than do their physicians. Disclosure of Interest: : E. Gvozdenovic: None declared, C. Allaart: None declared, R. Wolterbeek: None declared, C. Brenol: None declared, A. Chopra: None declared, M. Dougados: None declared, P. Emery: None declared, G. Ferraccioli: None declared, D. Van Der Heijde: None declared, T. huizinga: None declared, J. Kay: None declared, E. Mola: None declared, R. Moots: None declared, J. Da Silva: None declared, J. Smolen: None declared, D. Veale: None declared, R. Landewé Grant/research support: Pfizer DOI: 10.1136/annrheumdis-2014-eular.4982